Preparation and in vitro release of hydrochlorothiazide from gellan beads produced by ionotropic gelation - Emeje, M O; Eni-ike, N E; Brown, S A; Ofoefule, S I (Asian Journal of Pharmaceutics (AJP), 2014)
The inherent property of gellan gum to gel and form circular beads through a process of ionotropic gelation in the presence of cations was utilized in the formulation of hydrochlorothiazide (HCTZ).The prepared beads exhibited good drug entrapment efficiency, content uniformity, and sustained release potential. The gelatin-HCTZ beads could be utilized in the delivery of HCTZ, by which reduced frequency of the drug administration could be achieved.